The Joy of Knowledge Put Into Practice. The Cosmotechnical View on Acquiring Knowledge in Ancient China - András Áron IVÁCSON (Studia Universitatis Babeș-Bolyai. Philosophia)
Classical Chinese thought slowly formed from the 9th century BCE onward through the Spring and Autumn era but reached its pivotal point during the so-called Warring States era (5th to 2nd centuries BCE). According to historical records, during these three hundred years more than four hundred wars of different scales raged across the Chinese world. These wars brought with them their own consequences like famines and abject poverty, terrible inequality and disillusionment. An intellectual history forming in these conditions understandably and inevitably was influenced by these conditions. In this context, the Hong Kong philosopher Yuk Hui presents his thesis of “cosmotechnics”, the view that merely understanding the world is not enough, it is paramount to change it for the betterment of people’s lives. This is the theoretical underpinning of much of classical Chinese thought, according to Yuk Hui, and therefore also for the drive to acquire knowledge. Thus, one unique aspect of classical Chinese thought is its interminable insistence on how man’s every action must have a reason beyond that action itself and any sort of philosophizing that does not lead to practice in changing the environment for the good of the people inhabiting it, is a wasted and useless thought. Therefore, there are a number of words and concepts related to the acquisition of knowledge in Classical and modern Chinese, like “learning” 學, “teaching” 教, “discussion” 論, “argumentation” 辯, and so on, but all these are encompassed within “the way” 道, specifically the “correct way of doing a thing”, i.e.: actual practice, rather than mere thought alone. I aim to present several examples of this from remote Chinese antiquity and classical Chinese thought within the framework of what I term “cosmotechnical joy” stemming from making people’s lives better.